Didactic Principles of Teaching Music Sciences and Their Essence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the didactic principles involved in teaching music sciences and their underlying essence in the educational process. By examining the application of didactic theories in music education, the study highlights how these principles foster a more effective learning environment, enhance student engagement, and improve the understanding and retention of musical concepts. The research draws on both theoretical foundations and practical examples from music classrooms, discussing key didactic principles such as clarity, accessibility, activity, and individuality. The results demonstrate that adhering to these principles significantly impacts the effectiveness of music education. The article concludes by emphasizing the importance of a student-centered approach and the role of didactic principles in fostering musical skills, creativity, and critical thinking.